2016
DOI: 10.1002/cam4.697
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of multidrug resistance 1 expression by CDX2 in ovarian mucinous adenocarcinoma

Abstract: Epithelial ovarian cancer is an aggressive gynecological malignancy with a high mortality rate. Resistance against chemotherapeutic agents often develops in ovarian cancer patients, contributing to high recurrence rates. The multidrug resistance 1 (MDR1/ABCB1) gene encodes P‐glycoprotein, which affects the pharmacokinetic properties of anticancer agents. We previously reported that the Caudal‐related homeobox transcription factor CDX2 transcriptionally regulates MDR1 expression in colorectal cancer. CDX2 is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…The multidrug resistance genes MDR1 (also called ABCB1 ) and CFTR (also called ABCC7 ), coding for two ATP‐dependent drug efflux pumps, are transcriptional downstream targets of CDX2 (Kerschner and Harris, 2012; Koh et al ., 2016; Takakura et al ., 2010; Yan et al ., 2015). We found that both MDR1/ABCB1 and CFTR/ABCC7 were significantly downregulated in CDX2‐negative patient tumors and cell lines, independent of MSI status (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The multidrug resistance genes MDR1 (also called ABCB1 ) and CFTR (also called ABCC7 ), coding for two ATP‐dependent drug efflux pumps, are transcriptional downstream targets of CDX2 (Kerschner and Harris, 2012; Koh et al ., 2016; Takakura et al ., 2010; Yan et al ., 2015). We found that both MDR1/ABCB1 and CFTR/ABCC7 were significantly downregulated in CDX2‐negative patient tumors and cell lines, independent of MSI status (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed that CDX2 targets the multidrug resistance gene MDR1 (ABCB1) and CFTR (ABCC7), coding for two ATP-dependent drug efflet pumps [36][37][38]. These genes are significantly down-regulated in CDX2-negative cell lines and CDX2-negative patient tumors and have also been reported to promote the response to chemotherapy [24,38].…”
Section: Discussionmentioning
confidence: 99%
“…CDX2 may regulate cancer cell proliferation by suppressing transcriptional activity of the β-catenin-TCF complex and β-catenin nuclear localization (69). CDX2 also upregulates MDR1 by binding to its element in the promoter of the MDR1 gene, which may lead to drug resistance in mucinous ovarian cancer (70,71). Huaier (Trametes robiniophila Murr), a traditional Chinese medicine, and PPI, a component in the traditional Chinese medicinal herb Paris polyphylla Smith, have been reported to inhibit the nuclear translocation of β-catenin and to transcriptionally downregulate certain WNT/β-catenin target genes (LRP6, WNT5A and cyclin D1) (72).…”
Section: β-Catenin Modulators [Caudal Type Homeobox 2 (Cdx2) Huaiermentioning
confidence: 99%